Exploring the Role of Livestream Shopping and M-Commerce in Enhancing Humanitarian Logistics - Zaman , Sohaib uz; Junaid; Alam, Syed Hasnain; Khan, Umair Ahmed; Kamal, Muhammad Hassan (Pakistan Journal of Humanities and Social Sciences, 2025)
The purpose of this study is to examine the Livestream Shopping (Livestreaming) and M-Commerce adoption and their feasibility for enhancing Humanitarian Logistics in Pakistan. The research combines the Technology Acceptance model (TAM) and the Stimulus Organism Response model to understand consumer behavior, the digital engagement and the long term adoption trends understanding. Pakistani consumers engaged in digital transactions were surveyed using a quantitative, cross sectional design. The key factors influencing M Commerce adoption were analyzed in terms of key factors using SPSS and Partial Least Squares Structural Equation Modeling (PLS-SEM). These findings indicate how the perceived usefulness and social presence have a huge impact on consumers attitudes towards the use of the digital platforms. However, without trust or security concerns, merely ease to use does not equate adoption. Although there are many who express a hesitance in retail fraud, this agreement also shows the importance that more cybersecurity measures and trust building initiatives are underway. Additionally, digital engagement is even more influenced by behavioral intention of M-Commerce adoption as habit formation works only as a singular predictor of sustained engagement. The study serves as a call to develop regulatory frameworks as well as digital security measures and personalized consumer engagement strategies by governments and developers to create the ground to build that confidence in M-Commerce transactions. Moreover, M-commerce can also help the humanitarian logistics to provide a more efficient way of disaster response and region resource allocation. Further research should be conducted in longitudinal studies to investigate how future the transaction role of trust and habitual usage will play out. (219 WORDS)